Electrospray ion mobility spectrometry of intact viruses. Issue 1 (2004) - Thomas Thomas, John J. John J.; Bothner Bothner, Brian Brian; Traina Traina, Joe Joe; Benner Benner, W. Henry W. Henry; Siuzdak Siuzdak, Gary Gary
Abstract : Characterizing supramolecular interactions offers significant challenges using NMR or crystallographic techniques either because of size limitations or the difficulty in forming suitable crystals, while mass spectrometry is largely limited to low resolution mass information. Here we report gas phase measurements of intact virus particles using electrospray ion mobility spectrometry with an accuracy in radial measurements that were sufficient to differentiate closely related species. In addition, measured diameters indicate that iscosahedral virus particles retain their structure in the gas phase as well as undergoing a slight compaction in the absence of solvent. Analysis of the human pathogen adenovirus represents the largest and most sophisticated biomolecular complex detected in the gas phase to date. These results, on a diverse set of viral systems, suggest that ion mobility spectrometry may have broad applications for the analysis of biological complexes.